Characteristics Of Nasopharyngeal Carcinoma Patients In Indonesia - Innayaturrahmatiah Mujaddid; Ahmad Ardhani Pratama; Yarni Alimah (Sean Institute, 2025)
Nasopharyngeal carcinoma is a malignancy in the head and neck region that is always in the top five among other body part malignancies along with cervical cancer, breast cancer, lymph malignant tumors and skin cancer. The etiology of nasopharyngeal cancer is multifactorial including Epstein barr virus (EBV) infection, environmental such as exposure to carcinogens ( formaldehyde ), wood dust and firewood smoke, smoking, and diet. Other risk factors include age, gender, occupation and socioeconomic status. This study aims to determine the relationship between age and gender on the incidence of nasopharyngeal carcinoma. The method applied included an in-depth literature review relevant to the incidence of nasopharyngeal carcinoma. The identification process was conducted through online databases such as Google Scholar and Scopus. The results of the analysis showed that ages above 40 years had a higher risk of developing nasopharyngeal carcinoma. In addition, males were also found to be more susceptible to the disease than females. This study underscores the importance of understanding and treating nasopharyngeal carcinoma (NPC) by strengthening early detection programs aimed specifically at at-risk populations, especially individuals over 40 years old and lazy, who are shown to be at higher risk. In addition, it is important to improve public education on the risk factors for NPC, including early symptoms to look out for, so that people are more proactive in getting health checks.